Adherence with cardiovascular medications and the outcomes in patients with coronary arterial disease: “Real‐world” evidence - Chen, Chen; Li, Xiaoqing; Su, Yuhao; You, Zhigang; Wan, Rong; Hong, Kui (Clinical cardiology (Mahwah, N.J.), 2022)
Background Cardiovascular medications are vital for the secondary prevention of coronary arterial disease (CAD). However, the effect of cardiovascular medication may depend on the optimal adherence of the patients. This meta‐analysis aims to determine the magnitude of adherence to vascular medications that influences the absolute and relative risks (RRs) of mortality in patients with CAD in real‐world settings. Methods The Cochrane Library, PubMed, and EMBASE databases were searched through March 1, 2022. Prospective studies reporting association as RR and 95% confidence interval between cardiovascular medication adherence and any cardiovascular events and/or all‐cause mortality in patients with CAD were included. A one‐stage robust error meta‐regression method was used to summarize the dose‐specific relationships. Results A total of 18 studies were included. There is a significant inverse linear association between cardiovascular medication adherence and cardiovascular events (pnonlinearity = .68) or mortality (pnonlinearity = .82). The exposure‐effect analysis showed that an improvement of 20% cardiovascular medication adherence was associated with 8% or 12% lower risk of any cardiovascular events or mortality, respectively. In subgroup analysis, the benefit was observed in adherence of stain (RR: 0.90, for cardiovascular events, RR: 0.85, for mortality), angiotensin‐converting enzyme inhibitors (ACEI)/angiotensin II receptor blockers (ARB)(RR: 0.90, for mortality), and antiplatelet agent (RR: 0.89 for mortality) but not in beta‐blocker (RR: 0.90, p = .14, for cardiovascular events, RR: 0.97, p = .32 for mortality). Estimated absolute differences per 1 million individuals per year for mortality associated with 20% improvement were 175 cases for statin, 129 cases for antiplatelet, and 117 cases for ACEI/ARB. Conclusion Evidence from the real word showed poor adherence to vascular medications contributes to a considerable proportion of all cardiovascular disease events and mortality in patients with CAD.